Analisis Penerapan Blockchain Dalam Rangka Pencegahan Accounting Fraud - SE, Triantonno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Blockchain is a technology that features a distributed accounting systemthat is distributed among nodes. The Bitcoin cryptocurrency fintech is thefirst product that used a blockchain. This aim of this research is to find out the concept of blockchain implementation to prevent accounting fraud in a company. This research is a qualitative-explorative research with datacollection using documentation technique from related literatures. Theconclusion of this research is that blockchain can be used as alternativeprevention of accounting fraud. Blockchain can be utilized because there istransparency with the distributed system, which makes whistleblowingsystem more effective and independent, in fully applies the GCG principle.The concept that is offered is blockchain implementation within thecompany's internal or external scope. Keywords: Blockchain, Accounting Fraud, Implementation, Literature Study